2019
DOI: 10.1002/lary.28435
|View full text |Cite
|
Sign up to set email alerts
|

Intracapsular versus extracapsular dissection tonsillectomy for adults: A systematic review

Abstract: Objectives Tonsillectomy is an extremely common ENT surgical procedure. There is a growing interest in the role of intracapsular dissection tonsillectomy (ICDT) due to reported reduced perioperative complications. We aim to compare the outcomes associated with ICDT versus traditional extracapsular dissection tonsillectomy (ECDT) in the adult population. Methods Systematic review of all randomized controlled trials (RCTs) comparing ICDT and ECDT for all indications in the adult population. Electronic searches p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…These mainly include postoperative bleeding, postoperative infections and pain. The study participants will be recruited from a group of patients that would usually be operated on at our clinics according to common practice without any research setting, so the study itself does not add any risk for the participants as the novel TT seems to have fewer complications than the traditional TE [ 23 ]. In case of complications, participants are instructed to contact their respective clinic and their care is arranged by the study hospitals according to good clinical practice.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…These mainly include postoperative bleeding, postoperative infections and pain. The study participants will be recruited from a group of patients that would usually be operated on at our clinics according to common practice without any research setting, so the study itself does not add any risk for the participants as the novel TT seems to have fewer complications than the traditional TE [ 23 ]. In case of complications, participants are instructed to contact their respective clinic and their care is arranged by the study hospitals according to good clinical practice.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…While surgical instruments might influence the postoperative hemorrhage rate, the surgery technique is important as well. A systemic review [ 15 ] revealed that intracapsular dissection tonsillectomy has a lower secondary postoperative hemorrhage rate than extracapsular techniques. All patients in our study received extracapsular dissection tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported excellent symptom control, with similar trends for obstructive and infective conditions. 25 …”
Section: Discussionmentioning
confidence: 99%